Zika Virus Alters DNA Methylation of Neural Genes in an Organoid Model of the Developing Human Brain - Janssens, Sylvie (mSystems, 2018)
Zika virus (ZIKV) infection during early pregnancy can cause microcephaly and associated defects at birth, but whether it can induce neurologic sequelae that appear later in life remains unclear. Using a model of the developing brain based on embryonic stem cell-derived brain organoids, we studied the impact of ZIKV infection on the DNA methylation pattern across the entire genome in selected neural cell types. The virus unexpectedly alters the DNA methylome of neural progenitors, astrocytes, and differentiated neurons at genes that have been implicated in the pathogenesis of a number of brain disorders, most prominently mental retardation and schizophrenia. Our results suggest that ZIKV infection during fetal development could lead to a spectrum of delayed-onset neuropsychiatric complications. IMPORTANCE Scientific research on human neural stem cells and cerebral organoids has confirmed the congenital neurotropic and neurodestructive nature of the Zika virus. However, the extent to which prenatal ZIKV infection is associated with more subtle brain alterations, such as epigenetic changes, remains ill defined. Here, we address the question of whether ZIKV infection induces DNA methylation changes with the potential to cause brain disorders later in life.